2011
DOI: 10.1016/j.compscitech.2011.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Improving the flexural and thermomechanical properties of amino-functionalized carbon nanotube/epoxy composites by using a pre-curing treatment

Abstract: Please cite this article as: Prolongo, S.G., Gude, M.R., Ureña, A., Improving the flexural and thermomechanical properties of amino-functionalized carbon nanotube/epoxy composites by using a pre-curing treatment, Composites Science and Technology (2011), doi: 10.1016/j.compscitech.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 20 publications
4
47
2
Order By: Relevance
“…According to the dispersion state of the CNTs, different E 0 and loss modulus (E 00 ) behavior are expected (Hatakeyama and Quinn 1999;Li et al 2000;Mitchell et al 2002). Some studies report strong effect in the E 0 on the glassy state, due to improved interaction between the nanotubes and the EP matrix, which reduces the mobility of the EP matrix around the nanotubes and leads to an observed increase in thermal .7 ILSS before and after exposure for the unmodified and CNT-modified CFRP specimens reproduced after Barkoula et al (2009) stability (Valentini et al 2003;Gojny and Schulte 2004;Fidelusa et al 2005;Chen et al 2008;Prolongo et al 2011). A slight effect was measured on the rubbery state Prolongo et al 2011).…”
Section: Hygrothermal Response Of Carbon Nanotube Hybrid Aerospace Comentioning
confidence: 88%
See 1 more Smart Citation
“…According to the dispersion state of the CNTs, different E 0 and loss modulus (E 00 ) behavior are expected (Hatakeyama and Quinn 1999;Li et al 2000;Mitchell et al 2002). Some studies report strong effect in the E 0 on the glassy state, due to improved interaction between the nanotubes and the EP matrix, which reduces the mobility of the EP matrix around the nanotubes and leads to an observed increase in thermal .7 ILSS before and after exposure for the unmodified and CNT-modified CFRP specimens reproduced after Barkoula et al (2009) stability (Valentini et al 2003;Gojny and Schulte 2004;Fidelusa et al 2005;Chen et al 2008;Prolongo et al 2011). A slight effect was measured on the rubbery state Prolongo et al 2011).…”
Section: Hygrothermal Response Of Carbon Nanotube Hybrid Aerospace Comentioning
confidence: 88%
“…Some studies report strong effect in the E 0 on the glassy state, due to improved interaction between the nanotubes and the EP matrix, which reduces the mobility of the EP matrix around the nanotubes and leads to an observed increase in thermal .7 ILSS before and after exposure for the unmodified and CNT-modified CFRP specimens reproduced after Barkoula et al (2009) stability (Valentini et al 2003;Gojny and Schulte 2004;Fidelusa et al 2005;Chen et al 2008;Prolongo et al 2011). A slight effect was measured on the rubbery state Prolongo et al 2011). It was stated that the nanotube content was not sufficient (0.5 wt.%) to lead to any reinforcement since the molecular motion and the amplitude of this motion are very high and the macromolecule is not practically in contact with particles above the T g .…”
Section: Hygrothermal Response Of Carbon Nanotube Hybrid Aerospace Comentioning
confidence: 95%
“…Field emission gun SEM (FEG-SEM) micrographs showed that the degree of dispersion achieved for the pre-cured samples was better than that for the untreated samples [120].…”
Section: Solution Processingmentioning
confidence: 97%
“…Prolongo et al [120] studied the flexural properties of epoxy/amino-CNT composites prepared using a pre-curing treatment. As shown in Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation